2019
DOI: 10.1080/0284186x.2019.1598575
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis correlates with PD-L1 and PD-1 expression in lung adenocarcinoma

Abstract: Background: Predictive biomarkers for immunotherapy in lung cancer are intensively investigated; however, correlations between PD-L1/PD-1 expressions and clinical features or histopathological tumor characteristics determined on hematoxylin and eosin stained sections have not extensively been studied. Material and methods: We determined PD-L1 expression of tumor cells (TC) and immune cells (IC), and PD-1 expression of IC by immunohistochemistry in 268 lung adenocarcinoma (LADC) patients, and correlated the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
4
15
1
1
Order By: Relevance
“…Another interesting finding in the current study is the correlation of tumor necrosis and PD-L1 expression. These are in accordance to other studies that showed tumors with higher PD-L1 expression with a greater tendency to necrosis, a more aggressive tumor phenotype and higher proliferation rate ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another interesting finding in the current study is the correlation of tumor necrosis and PD-L1 expression. These are in accordance to other studies that showed tumors with higher PD-L1 expression with a greater tendency to necrosis, a more aggressive tumor phenotype and higher proliferation rate ( 39 , 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…The elevated expression of programmed cell death ligand 1 (PD-L1) has been demonstrated in KRAS-mutant cells, and it was also shown that ERK activation mediates the upregulation of PD-L1 by KRAS mutations [ 60 ]. On the contrary, Reiniger et al did not find significant relations between PD-L1 expression and KRAS status in LADC [ 61 ]. It was also reported that pembrolizumab (a PD-1 inhibitor) or an ERK inhibitor might prevent CD3+ T cells becoming apoptotic by recovering tumor immunity thus preventing immune escape [ 62 ].…”
Section: Predictive Role Of Kras Mutationsmentioning
confidence: 99%
“…Pembrolizumab has been approved as rst-line treatment for advanced PD-L1 positive NSCLC patients [29]. In our study, we found that high expression of PD-L1 was detected in 44.6% (29/65) cases of cavitary LUAD, signi cantly increased, compared to 20% (6/30) cases of noncavitary lung cancer, which demonstrated tumor necrosis correlates with higher PD-L1 expression in the LUAD [30]. Moreover, high expression of PD-L1 was correlated with high TNM stage, and could predict poor prognosis of patients with cavitary LUAD.…”
Section: Discussionmentioning
confidence: 53%